The purchase of organic fish in Bangladesh: Safeguarding against COVID-19 - Sheikh Ashiqurrahman Prince; Ishraat Saira Wahid (Cogent Business & Management, 2020)
Based on the theory of planned behaviour and cognitive dissonance, this research investigates how consumers' consciousness of the attributes of organic fish impacts the number of opportunities to purchase such fish at a safe social distance and how the consciousness of verbal recommendations affect the relationship between the consciousness of necessary social distance to safely buy organic fish and consumers' intention to purchase the fish. Applying these two theories and adding a new variable-social-distance purchasing-into the model, the research contributes significantly to current literature. Using a stratified random sampling, this research collected 320 data points from high, upper-middle and middle-income consumers that have been analysed through Amos Graphics and PROCESS macro in SPSS for the structural equation modelling. The findings of the research provide valuable insights to reduce the infection from COVID-19 as well as enhances the external validity and generalisability of the consumers' organic-food purchasing behaviour research.
Keywords: 650; COVID-19; organic fish; consciousness; social-distance purchasing; theory of planned behaviour; theory of cognitive dissonance